The COVID-19 Conundrum and the Lived Experiences of Indonesian Final Year University Students - Aulia Rahmawati (Arkus, 2023)
The overarching research on the COVID-19 pandemic is dominated by the science-medical research area. There is a lacuna of research addressing the social dimension of the pandemic in relation to everyday lives. This research has utilized Heideggerian hermeneutic phenomenology to address the question of “How do Indonesian final-year students deal with the pandemic, and how do they make sense of it through their lived experiences?”. Focus group discussions and in-depth interviews were generated in order to interview 24 final-year university students. The findings and discussion revealed that two major themes emerged: challenges and disappointments. The participants cited supervision problems along with unsupportive home situations and loneliness/isolation as the challenges during this pandemic. This research also explored the way in which a sense of disappointment lies within the displacement of their living events, such as the loss of a spatial identity which is represented by the university spaces, through to the missed chance of having a graduation ceremony. The COVID-19 pandemic is a spiraling conundrum wherein the physical dimension of health often eclipses the mental-psychological dimension. This research demonstrates that the lasting effect of the pandemic stretches beyond the materiality discourses of public health. The social dimensions of everyday living experiences should be taken into consideration by policymakers, including university boards, when formulating higher education policies during the pandemic.